Evolution of empiric vancomycin dosing in a neonatal population. (December 2018) - Radu, Luiza; Bengry, Tanner; Akierman, Albert; Alshaikh, Belal; Yusuf, Kamran; Dersch-Mills, Deonne
Abstract Background In 2014, we assessed the effectiveness of our neonatal vancomycin empirical dosing regimen (15–45 mg/kg/day) which led to development of a revised regimen (20–60 mg/kg/day). Objective To validate the revised empirical vancomycin dosage regimen in achieving target troughs. Methods The primary outcome of this multicenter retrospective before-and-after cohort study was the proportion of neonates in the present cohort achieving trough levels below, at or above target (<10, 10–20 and >20 mg/L). Secondary outcomes included difference between cohorts (historical and present) in mean troughs and proportion of patients achieving target levels. Results Out of 118 participants, 63 (53.39%) achieved target troughs, 44 (37.29%) had below target troughs and 11 (9.32%) reached above target levels. Mean trough levels and proportion of patients achieving target levels were higher in the present versus historical cohort (p  < 0.01 for all comparisons). Conclusions The revised empiric dosing regimen was more effective in achieving target serum trough concentrations.